Reflating Japan : Time to Get Unconventional? - Arbatli Saxegaard, Elif.; Botman, Dennis; Clinton, Kevin; Cova, Pietro (Washington, D.C. : International Monetary Fund, 2016)
Japan has ambitious economic goals: 3 percent nominal growth; 2 percent inflation; and a primary budget surplus. Abenomics has employed the three arrows of monetary, fiscal and structural policies, but the goals remain out of reach. We propose that countercyclical measures be embedded in long-run frameworks that anchor expectations for inflation and public debt. In addition, we argue for an incomes policy to assist reflation. Model simulations suggest that, combined, these proposals would make headway towards the goals, with, on balance, a better chance of success than the more unconventional policy alternatives proposed by Krugman, Svensson, and Turner from a risk-return perspective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet